Nanopartikel Daun Kelor (Moringa Oleifera Lamk.) terhadap Perubahan Kadar Kalsium Darah dan Tekanan Darah pada Wanita Usia Subur Hipertensi - Anis Styowati; Sri Sumarni; Diyah Fatmasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effectiveness of giving moringa leaf nanoparticles to changes in blood calcium levels and blood pressure in women of childbearing age with hypertension. The method used in this research is Quasi Experiment with Pretest–Posttest With a Control Group design. The results showed that the average increase in calcium levels in the intervention group after treatment was 0.49, and in the control group was 0.18. The average decrease in diastolic blood pressure was 18.50 mmHg in the intervention group and 6.81 mmHg in the control group. The average reduction in systolic blood pressure was 16.19 mmHg in the intervention group and 6.00 mmHg in the control group. In conclusion, the administration of moringa leaf nanoparticles effectively increases blood calcium levels and reduces blood pressure in women of childbearing age with hypertension. Keywords: Hypertension, Blood Calcium Levels, Moringa Leaf Nanoparticles, Blood Pressure, Women of Reproductive Age